Targeted therapy in pediatric central nervous system tumors: a review from the National Pediatric Cancer Foundation - Siegel, Benjamin I.; Patil, Prabhumallikarjun; Prakash, Akul; Klawinski, Darren M.; Hwang, Eugene I. (Frontiers in Oncology, 2025)
Central nervous system tumors represent the leading cause of cancer-related mortality in children. Conventional therapies of surgery, radiation, and cytotoxic chemotherapy have insufficient efficacy for some pediatric CNS tumors and are associated with significant morbidity, prompting an ongoing need for novel treatment approaches. Identification of molecular alterations driving tumorigenesis has led to a rising interest in developing targeted therapies for these tumors. The present narrative review focuses on recent progress in targeted therapies for pediatric CNS tumors. We outline the key implicated cellular pathways, discuss candidate molecular therapies for targeting each pathway, and present an overview of the clinical trial landscape for targeted therapies in pediatric CNS tumors. We then discuss challenges and future directions for targeted therapy, including combinatorial approaches and real-time drug screening for personalized treatment planning.